From matte banded to glossy black: Structures underlying colour change in the caudal lures of southern death adders (Acanthophis antarcticus, Reptilia: Elapidae) - Jenna Crowe-Riddell (2020)
Images of caudal lures (tail tips, n = 33) in a population of southern death adders, Acanthophis antarcticus .